Crossing the Boundaries of Medicinal Chemistry - Jakopin, Žiga (knjige, 2025)
The Section for Medicinal Chemistry of the Slovenian Pharmaceutical Society, the University of Ljubljana, Faculty of Pharmacy, and EATRIS (Node Slovenia) are delighted to welcome you to the second edition of the minisymposium on medicinal chemistry and related disciplines, Crossing the Boundaries of Medicinal Chemistry! It has been both a privilege and a pleasure to design this year’s scientific programme and carefully select the speakers who will join us. The symposium brings together a broad spectrum of topics, showcasing the latest advances in medicinal chemistry as well as insights from neighboring research areas. Our aim is to foster dynamic discussions, spark new ideas, and create opportunities for meaningful exchange. We hope the programme will not only capture your interest but also inspire and support your future endeavors. The symposium takes place in person, offering the invaluable chance to connect face-to-face, share ideas directly, and strengthen professional and personal ties. Beyond the lectures, we are particularly excited about the poster session - accompanied by refreshments - which we envision as a welcoming space for dialogue, collaboration, and networking.
Keywords: elektronske knjige; Farmacevtska kemija; Posvetovanja; zborniki